2017
DOI: 10.1080/08870446.2017.1314479
|View full text |Cite
|
Sign up to set email alerts
|

Moderation of the effects of discrimination-induced affective responses on health outcomes

Abstract: The current study (a) replicated previous research suggesting that two different types of affective reactions mediate the relations between perceived racial discrimination and physical health status vs. health-impairing behaviours: internalising and externalising, and (b) revealed moderation of these effects by coping mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 102 publications
2
28
0
Order By: Relevance
“…Several studies with FACHS adolescents have demonstrated significant relations between early PRD and health risk behaviors, including risky sex (Murry, Berkel, Brody, Gerrard, & Gibbons, 2007;Roberts et al, 2012) and substance use (Gibbons, Gerrard, VandeLune, Willis, Brody, & Conger, 2004). As expected, these latter relations are moderated by coping style; for example, the PRD/use relations are stronger for those who say they engage in avoidant coping (i.e., avoid thinking about or addressing problems they face; Gerrard, Gibbons, Fleischli, Cutrona, & Stock, 2018) and they are mediated by negative affect associated with the PRD (Gibbons et al, , 2012cf. Cuevas et al, 2014).…”
Section: Prd and Healthsupporting
confidence: 58%
“…Several studies with FACHS adolescents have demonstrated significant relations between early PRD and health risk behaviors, including risky sex (Murry, Berkel, Brody, Gerrard, & Gibbons, 2007;Roberts et al, 2012) and substance use (Gibbons, Gerrard, VandeLune, Willis, Brody, & Conger, 2004). As expected, these latter relations are moderated by coping style; for example, the PRD/use relations are stronger for those who say they engage in avoidant coping (i.e., avoid thinking about or addressing problems they face; Gerrard, Gibbons, Fleischli, Cutrona, & Stock, 2018) and they are mediated by negative affect associated with the PRD (Gibbons et al, , 2012cf. Cuevas et al, 2014).…”
Section: Prd and Healthsupporting
confidence: 58%
“…Both studies are examples of the importance of taking a nuanced approach to understanding how different types of affect predict health behaviours and how these relate to cognitive predictors . Gerrard, Gibbons, Fleischli, Cutrona, and Stock (2017) also demonstrate the importance of moving beyond main effects by examining mediation and moderation models to better understand the role of affect in health behaviours . They examined affect, including anxiety and depression as well as hostility and anger, as mediators of the effects of discrimination on health and health behaviours, as well as how coping styles moderate these pathways.…”
Section: Basic Empirical Papersmentioning
confidence: 99%
“…Finally, following the work of Bogart and colleagues (2013) , future research should further examine associations between discrimination and objective measures of health among HIV-positive Black and Latino men (e.g., CD4+, viral load; Bogart et al, 2013 ) as well as explore mediators and moderators of these relationships. Other potential mediators of the relationship between discrimination and physical health might include anger ( Brondolo et al, 2011 ; Gerrard et al, 2018 ; Gibbons et al, 2014 ), depression ( Gerrard et al, 2018 ; Gibbons et al, 2014 ), or negative health behaviors (e.g., substance use)/failure to engage in healthy behaviors ( Terra & Jules, 2002 ). Alternative moderators of this relationship might include other coping mechanisms than seeking social support (e.g., spirituality; Gerrard et al, 2018 ; Pascoe & Smart-Richman, 2009 ; Terra & Jules, 2002 ).…”
Section: Discussionmentioning
confidence: 99%
“…Social support may act as a moderator of the relationship between discrimination and physical health as well as of the mediating role of anxiety. Studies have demonstrated mixed evidence regarding the buffering effects of social support on the relationship between discrimination and mental (e.g., depression, anxiety) and physical health (e.g., self-rated health, cardiovascular reactivity to stress) among men and women of color ( Ajrouch, Reisine, Lim, Sohn, & Ismail, 2010 ; Brondolo, Ver Halen, Pencille, Beatty, & Contrada, 2009 ; Gerrard, Gibbons, Fleischli, Cutrona, & Stock, 2018 ; McNeil, Fincham, & Beach, 2014 ; Nadimpalli, James, Yu, Cothran, & Barnes, 2015 ); however, no studies have explored these associations in regard to HIV symptom burden.…”
mentioning
confidence: 99%